Atypical type A thymoma component identified by pulmonary metastasectomy 11 years after surgery of type AB thymoma - Makoto Hirai; Mikito Suzuki; Tomohiro Imoto; Reiko Shimizu; Masahiko Harada; Tsunekazu Hishima; Hirotoshi Horio (Respiratory Medicine Case Reports, 2023)
Atypical type A thymomas exhibit more aggressive features than conventional type A thymomas. Type AB thymomas rarely have atypical type A components. We report a rare case of type AB thymoma with an atypical type A component, that was identified after pulmonary metastasectomy 11 years after the primary surgery and long-term follow-up after recurrence.A 61-year-old female underwent extended thymectomy for an anterior mediastinal tumor 11 years prior and was diagnosed with type AB thymoma (Masaoka stage II). Five years ago, follow-up computed tomography showed well-circumscribed pulmonary nodules up to 1.0 cm in both lungs. All the pulmonary nodules grew slowly; however, one of the nodules grew to 1.6 cm, and thoracoscopic wedge resection was performed for diagnosis. Pathologically, the pulmonary nodule was consisted of type A thymoma component. Conventional type AB thymomas are usually locally aggressive neoplasms; thus, we reviewed the tissue slides of primary thymomas. Histologically, cytological atypia, hypercellularity, and increased mitosis are observed in the type A component. Consequently, the diagnosis was revised to a type AB thymoma with an atypical type A component. The pulmonary nodule exhibited the same atypical type A features. Pulmonary metastasectomy was performed two more times as volume-reduction surgery. The residual metastasis was located only in the lung with slow growth, 4 years after the first pulmonary resection; therefore, we followed up as an outpatient without treatment.